Validitas Modul Ajar Biologi Kelas X Berbasis Literasi Sains berbantuan E-Booklet - Sholihah, Fatikhatun Nikmatus; Wulandari, Anggun; Verawati, Ika (YASIN, 2025)
The Kurikulum Merdeka emphasizes project-based and differentiated learning tailored to students' individual characteristics. However, in the biodiversity topic at MAUWH, instruction remains conventional and has not yet integrated a scientific literacy approach, resulting in student disengagement and difficulty in grasping key concepts. This study aims to describe the validation results of a Grade X biology teaching module based on scientific literacy and supported by an e-booklet, as assessed by media and content experts. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The instruments used were validation questionnaires completed by two validators: a media expert and a content expert. Data were analyzed both qualitatively and quantitatively. The validation results showed a score of 86.67% from the media expert and 92.5% from the content expert, both falling into the "highly valid" category. These findings indicate that the scientific literacy-based teaching module supported by an e-booklet is suitable for use in Grade X biology instruction, particularly for the biodiversity topic, offering an innovative alternative that supports the implementation of Kurikulum Merdeka.